Cell-based analysis of Chikungunya virus E1 protein in membrane fusion - Kuo, Szu-Cheng (BioMed Central, 2012)
BACKGROUND: Chikungunya fever is a pandemic disease caused by the mosquito-borne Chikungunya virus (CHIKV). E1 glycoprotein mediation of viral membrane fusion during CHIKV infection is a crucial step in the release of viral genome into the host cytoplasm for replication. How the E1 structure determines membrane fusion and whether other CHIKV structural proteins participate in E1 fusion activity remain largely unexplored. METHODS: A bicistronic baculovirus expression system to produce recombinant baculoviruses for cell-based assay was used. Sf21 insect cells infected by recombinant baculoviruses bearing wild type or single-amino-acid substitution of CHIKV E1 and EGFP (enhanced green fluorescence protein) were employed to investigate the roles of four E1 amino acid residues (G91, V178, A226, and H230) in membrane fusion activity. RESULTS: Western blot analysis revealed that the E1 expression level and surface features in wild type and mutant substituted cells were similar. However, cell fusion assay found that those cells infected by CHIKV E1-H230A mutant baculovirus showed little fusion activity, and those bearing CHIKV E1-G91D mutant completely lost the ability to induce cell-cell fusion. Cells infected by recombinant baculoviruses of CHIKV E1-A226V and E1-V178A mutants exhibited the same membrane fusion capability as wild type. Although the E1 expression level of cells bearing monomeric-E1-based constructs (expressing E1 only) was greater than that of cells bearing 26S-based constructs (expressing all structural proteins), the sizes of syncytial cells induced by infection of baculoviruses containing 26S-based constructs were larger than those from infections having monomeric-E1 constructs, suggesting that other viral structure proteins participate or regulate E1 fusion activity. Furthermore, membrane fusion in cells infected by baculovirus bearing the A226V mutation constructs exhibited increased cholesterol-dependences and lower pH thresholds. Cells bearing the V178A mutation exhibited a slight decrease in cholesterol-dependence and a higher-pH threshold for fusion. CONCLUSIONS: Cells expressing amino acid substitutions of conserved protein E1 residues of E1-G91 and E1-H230 lost most of the CHIKV E1-mediated membrane fusion activity. Cells expressing mutations of less-conserved amino acids, E1-V178A and E1-A226V, retained membrane fusion activity to levels similar to those expressing wild type E1, but their fusion properties of pH threshold and cholesterol dependence were slightly altered.